DIMENSI MORAL YANG TERCERMIN DALAM SIKAP EMPATI BANGSA JEPANG - Sri Sudarsih (Diponegoro University, 2018)
Japan is a developed nation in a variety of fields. The key to success for the nation of Japan is inseparable from the attitude to life which respects its cultural values are realized in everyday life as the character education. This research emphasis on the attitude of empathy as a reflection of the morality of society Japan. The attitude of empathy is one of character education developed in Japan and must be instilled from an early age. The attitude of empathy because of friendship and togetherness that this high esteem is a value that becomes the cornerstone of people's lives so that Japan reached its former glory until now.Keywords: moral, empaty, character education.